Immune-nutritional status of celiac adults treated at the Institute of Gastroenterology, 2016-2017 - Deyanira La Rosa Hernández; Mailín Crespo Venegas; Lianelys Del Valle Rivera; Niurka Sánchez Castañeda (Universidad de Ciencias Médicas de La Habana, 2018)
Introduction: Celiac disease is one of the most common chronic disorders that affects people all over the world. The clinical evolution of these patients is compromised with the breakdown of the immune-nutritional balance. Objective:To characterize the immune-nutritional status of celiac adults treated at the Institute of Gastroenterology. Material and Methods: A cross-sectional descriptive observational study was conducted in 43 celiac adults treated at the Institute of Gastroenterology of Havana, in the period between March 2016-March 2017. With prior informed consent, all of them were given anthropometric measurements, dietetic survey, complete blood count, total doses of immunoglobulin, and biochemical studies. Results:The 53,5% of patients had some malnutrition disorders due to excess or defect. The 44%presented anemia, and the 14% presented hypercholesterolemia. IgM Hypogammaglobulinemia was observed in 9,3%; IgG and IgA Hypogammaglobulinemia were also observed in a 4,7% as well as 4,7% respectively. The most frequent personal pathological antecedent was that of giardiasis with 16,3%. No patient reported the intake of shellfish or cereals containing gluten, 9 were positive to tissue anti-transglutaminase, indicating poor dietary control, of which 88,8% of cases were detected in groups with a body mass index below the appropriate weight. Conclusions: Inadequate immuno-nutritional status is frequent in celiac adults treated in the Institute of Gastroenterology. Non-adherence to a gluten-free diet and the high frequency of malnutrition are present conditions in these patients. Keywords: celiac disease, immunonutrition, tissue anti-transglutaminase, gluten.